The Influence of Digital Marketing on Increasing MSME Income in Padang Panjang City - Resti, Okfi; Cindy, Cindy Pratiwi; Reni, Reni Febrina (El-kahfi | Jurnal Ekonomi Islam, 2025)
The development of technology makes digital marketing the key to MSME income. This article aims to explain the influence of digital marketing on increasing the income of MSMEs in Padang Panjang. The study used a quantitative approach. The technique used was distributing questionnaires to 100 MSME actors. Data processing using SPSS version 25 Pearson-Moment Correlation Coefficient model, analyzed using simple linear regression analysis, normality test, partial t-test, and determination test (R square ). The findings show that digital marketing has a regression coefficient of 13,204 on increasing MSME income with a significant level of 0.000 <0.05 which means it has an effect on MSME income. Based on the results of the regression analysis and the coefficient of determination, the influence of digital marketing is 29.2% on increasing MSME income in Padang Panjang. It is concluded that there is a positive and significant influence of the use of digital marketing on increasing MSME income in Padang Panjang.